The effects of P fertilizer addition on P transformations on high-P fixing and grassland soils - Pierzynski, Joy (Kansas State University, 2016)
Although phosphorus (P) is an essential nutrient for the growth of plants, it is one of the most limiting nutrients in terms of availability as a high proportion of applied P rapidly transforms into insoluble forms with low solubility in soils. To further understand the fate of P applied to soils, two separate but related studies using three high P-fixing soil types each were used for which the objectives were to investigate the mobility, availability, and reaction products from two granular and one liquid P fertilizer alone or plus a fertilizer enhancement product. Energy dispersive spectroscopy showed a substantial amount of P remained in the granule following a 5-week incubation. At the end of the 35-day incubation period there was evidence that the fluid fertilizer was superior over the granular sources in terms of enhanced diffusion and extractability of P for three calcareous soils with varying levels of CaCO₃. Phosphorus x-ray absorption near-edge structure (XANES) spectroscopy results in conjunction with resin-extractable P indicated a strong negative correlation between Ca-P solids formed and P extractability, suggesting that degree of Ca-P formation limits P solubility. For the three acidic P-fixing soils the results were complex. In two out of three acid soils, liquid P treatments diffused farther from the application point than the granular treatments. Phosphorus XANES results suggested that Fe-P or Al-P interactions control the overall P solubility. Integration of pH, resin extractable-P and XANES results suggested the P retention mechanism was either dominated by adsorption or precipitation depending on soil pH. More acidic soil conditions favored precipitation. The objectives of the third study were to observe how long-term (14 years) addition of P with or without N influences the inorganic and organic P pools in a native grassland soil using sequential fractionation, XANES, and ³¹P-nuclear magnetic resonance (NMR) spectroscopy. The overall results suggested that P and N fertilization and associated changes in plant productivity induced significant changes in soil P pools such as Ca-P, phytic acid, monoesters, and residual forms of P. The addition of P alone induced formation of inorganic P forms while the addition of P and N induced transformation of residual P forms into more labile and/or organic P forms.
Keywords: Soil phosphorus; High phosphorus-fixing soil; Soil phosphorus cycle; High phosphorus-fixing acid soil; High phosphorus-fixing calcareous soil; Tall grassland soils